Domain-Specificity of Educational and Learning Capital: A Study With Musical Talents - Reutlinger, Marold; Pfeiffer, Wolfgang; Stoeger, Heidrun; Vialle, Wilma; Ziegler, Albert (Frontiers in Psychology, 2020)
The Education and Learning Capital Approach (ELCA) has been widely used to investigate talent development. A research gap is the so far only implicit consideration of the domain specificity of educational and learning capital. In an empirical study with 365 school students we investigated the domain specificity of the approach for the domains of school learning and learning to play a musical instrument. At the beginning of the school year, students filled out a version of the Questionnaire for Educational and Learning Capital (QELC) for both domains and also responded to other domain-related measures (self-efficacy, grades). Six weeks later, students filled out a learning diary for one week in which they reported their activities on an hourly basis and responded to questions concerning these activities. Based on the Sociotope Approach this procedure helped to identify times in which students actually practiced their musical instrument, times that students could potentially practice their musical instrument (objective action space), and times that students would be expected to practice their musical instrument (normative action space). Three hypotheses were tested and could be confirmed: First, the availability of educational and learning capital for school learning and learning an instrument differed. Second, a confirmatory factor analysis confirmed the factorial validity of the domain-specific capital measurements. Third, domain-congruent correlations were mostly higher than domain-incongruent correlations, i.e., the availability of educational and learning capital for school learning correlated more closely with variables related to school learning than with variables related to learning a musical instrument. Similarly, the availability of the capitals for learning a musical instrument correlated more closely with variables related to learning a musical instrument.